Indonesian – English Code-Mixing in Novel Touché by Windhy Puspitadewi - Meigasuri, Zawranisa; Soethama, Putu Lirishati (Humanis, 2020)
This studyaims to find out the types of code-mixing, to identify word classcategories of the words being mixed, and to explain the factors of using mixed languages in Touché novel.Data were taken from Touché novel by WindhyPuspitadewi and were collected by using documentation method. The sample data were selected by using purposive sampling method. This study used qualitative method to analyze the data and the results are presented in formal and informal method. In order to analyze the code-mixing, the theory of factors in using code-mixing proposed by Tej K. Bhatia and William C. Ritchie (2013) was used. The result showed that from 85 Indonesian – English code-mixing data that had been collected, it was found that 39 data are insertion code-mixing, 36 data are alternation code-mixing and 10 data are congruent lexicalization. The categories of words being mixed are varied such as words (i.e. nouns, adjectives, etc.), phrases (i.e. noun phrases, adverb phrases, etc.), and clauses (i.e. dependent and independent clauses). There are four factors found in using code-mixing in the novel: social roles and relationships of participants, situational factors, message-intrinsic factors, and language attitudes, dominance and security.